2015
DOI: 10.1093/mnras/stv1399
|View full text |Cite
|
Sign up to set email alerts
|

The mass function of hydrogen-rich white dwarfs: robust observational evidence for a distinctive high-mass excess near 1 M

Abstract: The mass function of hydrogen-rich atmosphere white dwarfs has been frequently found to reveal a distinctive high-mass excess near 1 M ⊙ . However, a significant excess of massive white dwarfs has not been detected in the mass function of the largest white dwarf catalogue to date from the Sloan Digital Sky Survey. Hence, whether a high-mass excess exists or not has remained an open question. In this work we build the mass function of the latest catalogue of data release 10 SDSS hydrogenrich white dwarfs, inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 59 publications
4
32
1
Order By: Relevance
“…The cumulative distance distribution for our DA and non-DA samples follow a cubic rule up to 110 pc, indicating that our sample should be near complete up to this distance in the SDSS spectroscopic cone Holberg et al 2016). To ensure the reliability of our results we present our determinations for a close to complete sample corrected by the observed volume, following Schmidt (1968Schmidt ( , 1975; Green (1980); Stobie et al (1989); Liebert et al (2003); Kepler et al (2007); Limoges & Bergeron (2010); Rebassa-Mansergas et al (2015), limiting the magnitude on SDSS filter g, 14.5 < mg < 19.0, and assuming a galactic disk scale height of 300 pc. The resulting sample after applying the magnitude limits for the correction is composed of 5 336 DAs and 1 315 non-DAs.…”
Section: Distance Distribution and Completenessmentioning
confidence: 86%
“…The cumulative distance distribution for our DA and non-DA samples follow a cubic rule up to 110 pc, indicating that our sample should be near complete up to this distance in the SDSS spectroscopic cone Holberg et al 2016). To ensure the reliability of our results we present our determinations for a close to complete sample corrected by the observed volume, following Schmidt (1968Schmidt ( , 1975; Green (1980); Stobie et al (1989); Liebert et al (2003); Kepler et al (2007); Limoges & Bergeron (2010); Rebassa-Mansergas et al (2015), limiting the magnitude on SDSS filter g, 14.5 < mg < 19.0, and assuming a galactic disk scale height of 300 pc. The resulting sample after applying the magnitude limits for the correction is composed of 5 336 DAs and 1 315 non-DAs.…”
Section: Distance Distribution and Completenessmentioning
confidence: 86%
“…Recently, Maoz et al (2018) claimed that up to a ∼10 per cent of the observed single white dwarfs are expected to be the result of binary white dwarf mergers, thus significantly contributing to the massive content of these objects. Alternatively, binary scenarios such as the merger of the degenerate core of a giant star with a main-sequence or a white dwarf companion (Rebassa-Mansergas et al 2015b) have also been proposed. Other possibilities, which are not a priori disposable, also exist.…”
Section: The Physical Properties Of the 100 Pc Gaia White Dwarfsmentioning
confidence: 99%
“…Figure 3 shows that the core convective region is restricted to mass coordinates below ≈0.5 M e for stars of M  2.5 M e . Using the MS-WD mass relation of Renedo et al (2010) and Andrews et al (2015), these low-mass stars account for the majority of WDs, whose mass distribution peaks near 0.6 M e (Rebassa- Mansergas et al 2015). Since the ohmic diffusion time is very long in WDs (Ferrario et al 2015a), we expect that core-dynamo-generated fields are unlikely to be visible at the surface of most WDs.…”
Section: Magnetic Fields In Wdsmentioning
confidence: 99%